Howard Jacobson - Brauner, David, 1968- (Manchester : Manchester University Press, 2020)
This is a comprehensive and definitive study of the Man Booker Prize-winning novelist, Howard Jacobson. It offers lucid, detailed and nuanced readings of each of Jacobson's novels, and makes a powerful case for the importance of his work in the landscape of contemporary fiction.
Front matter -- Cover -- Half-title -- Series page -- Title page -- Copyright page -- Dedication -- Contents -- Series editor's preface -- Acknowledgements -- Introduction -- 'Being funny': comedy, the anti-pastoral and literary politics -- 'Being men': masculinity, mortality and sexual politics -- 'Being Jewish': Philip Roth, antisemitism and the Holocaust -- Afterword -- Select bibliography -- Index
Includes bibliographical references and index.
Online resource; title from PDF title page (JSTOR, viewed May 10, 2021).
English.
JSTOR
Keywords: Jacobson, Howard -- Criticism and interpretation; Jacobson, Howard -- Criticism and interpretation; Jacobson, Howard; Modern & Contemporary Fiction (Post C 1945); BIOGRAPHY & AUTOBIOGRAPHY -- Literary Figures; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Literary theory; Criticism, interpretation, etc